At Odds:: Reviewers and Readers of the Jalna Novels - Panofsky, Ruth (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
Although Mazo de la Roche was criticized by reviewers, the author enjoyed an enduring and gratifying relationship with her innumerable readers. The immediate attempt to place de la Roche's novel in the canon of "great works" was due largely to two factors. First, since the novel had won a substantial sum for an unfamiliar author, it had to be perceived as excellent. Second, since the award had been offered by the Atlantic Monthly, the status of the magazine was reflected in its choice of winner. Notions of literary value, as well as ideological assumptions, held respectively by reviewers and readers diverged over time and resulted in the gradual shift in de la Roche's literary standing. In reconstructing the historical moment of Jalna, the paradox of professional marginalization and popular success emerges, despite an early acceptance by both high and popular cultures. For de la Roche's readers, the conservatism of her novels evoked a past — albeit a largely imaginary one — that they found particularly appealing. Her reviewers, on the other hand, were frustrated by a series of novels that embraced an increasingly obsolete ideology.